Unveiling the role of ASPP1 in cancer progression: pan-cancer bioinformatics and experimental validation in colorectal cancer - Keyuan Xiao; Xiang Li; Ihsan Ullah; Wenqing Hu; Kaiqiang Wang; Fan Yang; Chengyu Yang; Chunqi Feng; Liang Zong; Xinghua Li (Frontiers in Oncology)
BackgroundThe Apoptosis-Stimulating Protein of P53 (ASPP) family contributes to apoptosis regulation and tumor suppression, with ASPP1 influencing processes like cancer cell proliferation, invasion, and migration. Its expression varies across cancer types, suggesting a potential role in oncogenesis.MethodsThis study investigates ASPP1’s role across various cancers using a comprehensive bioinformatics approach. Data were extracted from public resources, including The Cancer Genome Atlas (TCGA), GTEx, and the Human Protein Atlas, and analyzed via tools such as cBioPortal, GEPIA, and TIMER2. Statistical and network analyses were performed with R, Cytoscape, and Hiplot. ASPP1’s function in colorectal cancer was further explored through in vitro assays, including qRT-PCR, Western blotting, colony formation, Transwell, and wound healing.ResultsASPP1 expression exhibited significant variability across different cancer types, with marked associations with patient outcomes, particularly overall survival (OS) and disease-specific survival (DSS) across several cancer types. In-depth protein-protein interaction (PPI) analysis revealed ASPP1’s involvement in apoptosis and cancer progression networks. Functional enrichment analysis further linked ASPP1 to key apoptotic signaling pathways and transcriptional regulatory processes, underscoring its potential impact on tumor biology. Additionally, the expression of ASPP1 correlates with immune cell infiltration patterns, including cancer-associated fibroblasts and various immune markers, suggesting roles in immune response modulation. In vitro assays with colorectal cancer cell lines revealed significantly lower ASPP1 expression levels compared to normal colon cells (HCM460), and ASPP1 overexpression experiments showed a marked reduction in colorectal cancer cell proliferation, colony formation, invasion, and migration abilities. These cellular findings align with the bioinformatics predictions, highlighting ASPP1’s role as a suppressor of metastatic traits in colorectal cancer.ConclusionThis study highlights ASPP1 as a forecasting biomarker in the colorectal cancers and potentially across other cancers. The findings support ASPP1’s involvement in tumor biology, particularly regarding cell proliferation and metastatic potential, establishing a foundation for further investigation into its therapeutic relevance.